2020
DOI: 10.1080/2162402x.2020.1758547
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor promotes degradation of STAT2 to inhibit the interferon response in breast cancer

Abstract: Type I (IFNα/β) interferon signaling represents a critical transduction pathway involved in recognition and destruction of nascent tumor cells. Downregulation of this pathway to promote a more immunosuppressed microenvironment contributes to the ability of tumor cells to evade the immune system, a known Hallmark of Cancer. The present study investigates the progesterone receptor (PR), which is expressed in the vast majority of breast cancers, and its ability to inhibit efficient interferon signaling in tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Thus, low MYC targets and androgen response 35 , two transcriptional signatures, which themselves may reflect low PR signaling activity, are associated with an increased transcriptional and proliferative response upon P4 stimulation suggesting that increased, PR signaling activity renders cells insensitive to the ligand. The differential enrichment of the immunomodulatory pathways, TNFα and INFα signaling suggest close crosstalk between the pregnancy hormone and the innate immune response as reported recently 36 , 37 .
Fig.
…”
Section: Resultssupporting
confidence: 72%
“…Thus, low MYC targets and androgen response 35 , two transcriptional signatures, which themselves may reflect low PR signaling activity, are associated with an increased transcriptional and proliferative response upon P4 stimulation suggesting that increased, PR signaling activity renders cells insensitive to the ligand. The differential enrichment of the immunomodulatory pathways, TNFα and INFα signaling suggest close crosstalk between the pregnancy hormone and the innate immune response as reported recently 36 , 37 .
Fig.
…”
Section: Resultssupporting
confidence: 72%
“…Our data revealed that the luminal tumor co-marker progesterone receptor (PR), which is linked to an immunosuppressive tumor microenvironment [ 55 , 56 ], displayed a decrease in expression at the highest significance as compared to the cold subgroup ( Figure 4 B,C). Another contemplated immunomodulation factor is the PPARγ/RXRα pathway, which regulates cell proliferation and inflammation [ 57 ].…”
Section: Resultsmentioning
confidence: 98%
“…Our data revealed that the luminal tumour co-marker progesterone receptor (PR), which is linked to an immunosuppressive tumour microenvironment [47, 48], displayed a decrease in expression at the highest significance as compared to the cold subgroup (Figure 4B, C). Another contemplated immunomodulation factor is the PPARγ/RXRα pathway which regulates cell proliferation and inflammation [49].…”
Section: Resultsmentioning
confidence: 99%